Childhood and/or Adolescence Bullying Victimization and Trajectories of Hard Drug Use from Late Adolescence to Young Adulthood - Guo, Siying (Victims & offenders, 2022)
The study aimed to identify developmental trajectories of hard drug use throughout late adolescence and into early adulthood and assess the unique and joint contribution of bullying victimization occurred in childhood and/or adolescence to the development of hard drug use. Using group-based trajectory modeling and multinomial logistic regression, the current study analyzed the data from the National Longitudinal Survey of Youth 1997 to investigate these phenomena. Results indicated that a four-group trajectory model best fit the data of hard drug use. Bullying victimization was important in understanding the developmental trajectories of hard drug use. Its effect differed by when the victimization occurs, in childhood only, in adolescence only, or in both. There is a great need to intervene with those being repeatedly bullied as early as possible in order to reduce the likelihood of hard drug use.